Chapter Introduction - Rein, Katharina (Taylor & Francis, 2023)
This chapter introduces the topic of this book and gives an overview over the themes addressed in the following chapters. It discusses and clarifies the central terms of the project such as the main terms in the book title, which refers to various kinds of techniques of illusion, and the distinction between magic, tricks, and illusions. This chapter also examines the concept of willing suspension of disbelief that is often used to explain the reception of magic for entertainment purposes, and clarifies some of the jargon used by magicians to distinguish various kinds of illusions in order to introduce the focal point of the book: modern, technology-based stage magic. After a critical reflection on issues concerning the race and gender of the protagonists of this book and their historical visibility and determinations, this chapter also lays out the time and space of the stories told in this book. It concludes with an overview over the book's contents and structure as well as the materials used and the archives consulted in the course of this research project.